(3UahI GdbQi aj UaI MLI GdeUWaj hWhGag HCe GdbQis - (3CMeO Hf YHO Gddg Hf eMeO GdWHQj, CHh GdYHGS, eMH GdOjf,J (B694 (3g` s ((3eMeO Hf eMeO Hf efUhQ Hf gGTe GdMSjfi GdehShi GdMdHi s)
(3ChdgG (B:s
(3GdMeO ddg hdGfYHO EdG EjGg s
(3BNQgG (B:s
(3gPG BNQ eG JjSQ ef JdNjU UaI MLJg Udi Gddg Ydjg hSde hddg GdMeO hGdefI s
(3Vef eLehY s
(3HBMQgG SeGY ai YOI eLGdS BNQgG ai (B19 (3LeGOi GdChdi SfI (B881(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B324 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B281s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B92 s
Keywords: (3GdJGQjNs